Al-Ghazali on The Method of Achieving Happiness - Soleh, Achmad Khudori (Psikoislamika: Jurnal Psikologi Islam, 2023)
Happiness can give immunity to the individual’s physical and psychological so that they become strong in facing pressure. In severe social and psychological conditions, happiness becomes essential and needed. This study aims to analyze al-Ghazali's concept of achieving happiness. The research uses the content analysis method with primary sources as the main reference. The research results show that achieving happiness in al-Ghazali consists of three stages. Namely, (1) recognizing one’s nature and character, (2) placing the heart as a leader, (3) directing attention to God. This stage necessitates studies on self and psychology, essential for cleansing the soul. In management, al-Ghazali's concept of heart leadership is in harmony with al-Farabi's leadership theory, which states that leaders must be able to direct their subordinates to happiness. The implication of this concept is that there is a holistic approach to improving the quality of human life as a whole in the fields of psychology, education and spirituality. Ultimately, all potential and activity must be directed to God as the source of happiness to achieve true happines.Keywords: al-Ghazali; Happiness; Know Yourself; Leadership of the Heart